PH-Dependent Protonation of Histidine Residues Is Critical for Electrostatic Binding of Low-Density Lipoproteins to Human Coronary Arteries. Issue 8 (2nd June 2022) - Glise, Lars; Rutberg, Mikael; Håversen, Liliana; Levin, Malin C.; Levin, Max; Jeppsson, Anders; Borén, Jan; Fogelstrand, Per
Abstract : Background: The initiating step in atherogenesis is the electrostatic binding of LDL (low-density lipoprotein) to proteoglycan glycosaminoglycans in the arterial intima. However, although proteoglycans are widespread throughout the intima of most coronary artery segments, LDL is not evenly distributed, indicating that LDL retention is not merely dependent on the presence of proteoglycans. We aim to identify factors that promote the interaction between LDL and the vessel wall of human coronary arteries. Methods: We developed an ex vivo model to investigate binding of labeled human LDL to human coronary artery sections without the interference of cellular processes. Results: By staining consecutive sections of human coronary arteries, we found strong staining of sulfated glycosaminoglycans throughout the arterial intima, whereas endogenous LDL deposits were focally distributed. Ex vivo binding of LDL was uniform at all intimal areas with sulfated glycosaminoglycans. However, lowering the pH from 7.4 to 6.5 triggered a 35-fold increase in LDL binding. The pH-dependent binding was abolished by pretreating LDL with diethyl-pyrocarbonate, which blocks the protonation of histidine residues, or cyclohexanedione, which inhibits the positive charge of site B on LDL. Thus, both histidine protonation and site B are required for strong electrostatic LDL binding to the intima. Conclusions: This study identifies histidine protonation as an important component for electrostatic LDL binding to human coronary arteries. Our findings show that the local pH will have a profound impact on LDL's affinity for sulfated glycosaminoglycans, which may influence the retention and accumulation pattern of LDL in the arterial vasculature.